Abnormal lithium isotope composition from the ancient lithospheric mantle beneath the North China Craton - Tang, Yan-Jie (Nature Publishing Group, 2014)
Lithium elemental and isotopic compositions of olivines in peridotite xenoliths from Hebi in the North China Craton provide direct evidence for the highly variable δ(7)Li in Archean lithospheric mantle. The δ(7)Li in the cores of olivines from the Hebi high-Mg# peridotites (Fo > 91) show extreme variation from −27 to +21, in marked deviation from the δ(7)Li range of fresh MORB (+1.6 to +5.6) although the Li abundances of the olivines are within the range of normal mantle (1–2 ppm). The Li abundances and δ(7)Li characteristics of the Hebi olivines could not have been produced by recent diffusive-driven isotopic fractionation of Li and therefore the δ(7)Li in the cores of these olivines record the isotopic signature of the subcontinental lithospheric mantle. Our data demonstrate that abnormal δ(7)Li may be preserved in the ancient lithospheric mantle as observed in our study from the central North China Craton, which suggest that the subcontinental lithospheric mantle has experienced modification of fluid/melt derived from recycled oceanic crust.